Art Conservator : The Bulletin of the Williamstown Art Conservation Center. (Williamstown-Massachusetts : Williamstown Art Conservation Center, 2006)
Art Conservator, is a biannual publication which covers various aspects of treatment methodology, technical analysis, and research carried out by conservators in both our Williamstown and Atlanta centers. Art Conservator was founded in 2006: its full-color photography, innovative features, and accessible articles illustrate the conservation process and describe practical and theoretical issues facing the preservation of our cultural heritage. Each installment also contains a Technical Bulletin prepared by one of our staff conservators, which delves in-depth into a topic of importance to museum professionals and others working with cultural objects.(williamstownart.org)
Online: https://williamstownart.org/publications
Engels
Tijdschriften
Keywords: restauratie; conservatie; Williamstown Art Conservation Center